Fanzine e design gráfico: exercícios de autonomia e criação - BASAGLIA, Ana Paula Hoffmann Frittoli (2016)
This paper aims to show the potential of fanzines production as a means of creativity and critical expression, analyzing the arts produced by a group of students in a public school in São Paulo/SP, after reflections on graphic design concepts, fanzine, literacy and visual culture, image reading, autonomy. Fanzine is commonly associated with an alternative publication without commercial value and usually amateur production nature and, because of these qualities, can be developed easily in school. The goal is to show that working with fanzines allows students to take their role as subjects in the process of understanding and building values; pointing out that working with fanzines, and their meanings from its form and content,are extremely personal and graphic objects lend themselves to communicate in an original and authentic way; demonstrate that graphic design is a powerful tool for communication and knowledge can help people to have more say in a collective experimentation space.